Iron status and developmental delay among children aged 24–36 months - Jessica Ferdi; Saptawati Bardosono; Bernie Endyarni Medise (Paediatrica Indonesiana, 2022)
Background Optimal child development is needed for adequate learning. Children, particularly toddlers, require iron for brain development, and consequently, overall development. Objective To analyze for an association between iron status and developmental status in children aged 24–36 months. Methods This explorative cross-sectional study was held in Kampung Melayu, Jakarta. Subjects were recruited using a total population sampling method. Data were collected through interview with parents, anthropometric examinations, and blood tests. Developmental status was determined using the Ages and Stages Questionnaire-3 (ASQ-3) and iron status was based on ferritin, high sensitivity C-reactive protein (hs-CRP), and hemoglobin levels. Data analyses included Chi-square/Fisher’s exact, Mann-Whitney, and logistic regression tests. Results Of 80 subjects, 17.5% had developmental delay and 41.3% had deficient iron status. There was no significant association between iron status and developmental status in bivariate analysis, but the logistic regression analysis revealed that iron status (OR=6.9; 95%CI 1.328 to 35.633; P=0.022) and nutritional status (OR=11.75; 95%CI 1.551 to 88.979; P=0.017) contributed to developmental delay. Conclusion Better iron status and nutritional status are associated with better child development of children aged 24–36 months. So efforts are needed to maintain iron status as well as nutritional status.